Islamic finance and Sustainable Development Goals. A bibliometric analysis from 2000 to 2021 - Lanzara, Federica (European Journal of Islamic Finance, 2021)
The aim of this research is to provide, through a bibliometric analysis of the last 21 years of thematic literature, an overview on the contribution of sustainable development goals (SDGs) to the discussion in the field of Islamic finance. A bibliometric method has been used to analyze the characteristics, citation patterns and content of 15 documents published in international academic journals, books review and chapters, editorial material and proceedings papers. Considering the findings, the analysis has shown that there is an enormous gap on that field, with a few works on the topic with an impact on research. Through the analysis of the papers, it emerges that qualitative method is the most used method to demonstrate the link between Islamic finance and its relationship in the achievement of sustainable development goals. The research also shows that there is an increase on the academic interest on the topic only in the last four years. Research limitations/implications – The study highlights a limitation, related to the adoption of the bibliometric method. This is due to the fact that databases include only part of the scientific papers and not all world’s sources. However, WOS database, the one adopted for the research, is the world’s most complete index even if it is not complete at all. On the other hand, to have a wider landscape of knowledge on the field of research, they have been considered all kind of sources: books review, chapters, papers published in international and academic journals, editorial materials, reviews and proceedings papers. Originality/value – This research shows the initial attention of the academic world toward the relation between Islamic finance and Sustainable Development Goals, however underlying that this contribution is not systematically interpreted by the different stakeholders and in the different countries. The bibliometric analysis of the literature puts Islamic finance and Sustainable Development Goals in relation but contemporarily indicates that more efforts need to be done in order to enhance this bond both from an academical and a practical point of view. Therefore, with the intention of mapping all the studies that have been done in this regard, the study analyzes how research on the relationship between Islamic finance and social development goals has been addressed, confirm with its qualitative approach the link between Islamic finance and social impact.